Management of Facilities and Infrastructure in Improving The Quality of Islamic Education - Muchlis Anshori; Slamet Suwarno; Kasbani Kasbani (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
This article aims to describe the implementation of infrastructure management in improving the quality of Islamic education in Madrasahs. This article uses descriptive qualitative research methods to obtain findings and information related to infrastructure management at MTs Ponpes Al-Iman Muntilan. The purpose of the study was to describe the management of facilities and infrastructure carried out at MTs Ponpes Al-Iman Muntilan, as a madrasa based in Islamic boarding schools. From this research, the following findings were obtained; In the management of the maintenance of facilities and infrastructure, MTs Ponpes Al-Iman Muntilan not only submits to certain teachers or special officers but also involves students directly to practice independence and a sense of belonging so that students feel they have a responsibility, although on the other hand there are also drawbacks. due to time constraints of students. In addition, in the inventory, the management has not deleted the recording of the inventory of facilities and infrastructure because they still prioritize the principle of benefit, as long as they can be used, the facilities and infrastructure are still used. This was done due to budget constraints.